Impact of overt diabetes diagnosed in pregnancy in a multi-ethnic cohort in Spain. (3rd April 2019) - Mañé, Laura; Flores-Le Roux, Juana Antonia; Benaiges, David; Chillarón, Juan José; Prados, Montse; Pedro-Botet, Juan; Llauradó, Gemma; Gortazar, Lucía; Payà, Antonio
Abstract: Overt diabetes (ODM) is defined as women without diabetes meeting the criteria for diabetes at the first antenatal visit. The risk of obstetric complications increases linearly with maternal glycemia and poorer maternal-fetal outcomes than in gestational diabetes (GDM) may be expected. Studies focusing on ODM pregnancy outcomes are lacking. We aimed to analyze maternal characteristics and pregnancy outcomes in ODM women compared with those with GDM. A retrospective cohort study of women giving birth between January 2010 and April 2013 was conducted. Participants with pre-gestational diabetes were excluded. All women underwent screening for GDM at the 24th–28th weeks of gestation or at the first prenatal visit in those with risk factors. HbA1c and a fasting glucose were measured in GDM women to rule out ODM. Of the 5, 633 women included, 572 (10%) were diagnosed with GDM and 50 (0.88%) with ODM. Almost 95% of ODM women were from ethnic minorities. After adjustment for confounding factors, ODM women showed increased rates of premature birth (23.1% vs. 6.7%, p < .001), emergent cesarean section (41.0% vs. 19.5%, p = .049), preeclampsia (22% vs. 3.7%, p < .001) and large-for-gestational-age babies (40.0% vs. 14.8%, p = .008) compared with GDM. In conclusion, ODM is associated with poorer obstetric outcomes than GDM and affects mainly women from ethnic minorities.